Penerapan Strategi Pembelajaran Berbasis Kepedulian Lingkungan untuk Meningkatkan Karakter Peduli Lingkungan Siswa Kelas III SD Negeri 133 Parmompang - Siti Marwiyah; Ali Yusron; Marwah Lubis (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: This study aims to analyze the strategies of classroom teachers in fostering environmental awareness among third-grade students at SD Negeri 133 Parmompang and identify factors that support and hinder its implementation. The study used a qualitative descriptive approach with third-grade teachers, principals, and students as subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that teachers implemented direct learning strategies, role models, habituation through routine "Clean Saturday" activities, contextual learning, project-based learning, and spontaneous activities in the form of providing motivation, rewards, and reprimands. These implementation strategies were evident in student involvement in classroom cleaning activities, caring for school plants, using positive habits in daily interactions, and participating in school greening activities. Supporting factors for the implementation of the strategies included the principal's support, the availability of facilities and infrastructure, supportive school programs, and cooperation between students. Meanwhile, inhibiting factors included low awareness among some students, limited learning time, the influence of the environment outside the school, and limited certain facilities. Research findings show that the formation of environmentally conscious character in elementary school students requires the implementation of diverse, consistent strategies that are integrated with school culture so that environmental values can be internalized in students' daily activities.Abstrak: Penelitian ini bertujuan untuk menganalisis strategi guru kelas dalam menumbuhkan karakter peduli lingkungan pada siswa kelas III SD Negeri 133 Parmompang serta mengidentifikasi faktor-faktor yang mendukung dan menghambat pelaksanaannya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek penelitian guru kelas III, kepala sekolah, dan siswa. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa guru menerapkan strategi pembelajaran langsung, keteladanan, pembiasaan melalui kegiatan rutin “Sabtu Bersih”, pembelajaran kontekstual, pembelajaran berbasis proyek, serta kegiatan spontan berupa pemberian motivasi, penghargaan, dan teguran. Implementasi strategi tersebut terlihat dari keterlibatan siswa dalam kegiatan kebersihan kelas, perawatan tanaman sekolah, penggunaan kebiasaan positif dalam interaksi sehari-hari, serta partisipasi dalam kegiatan penghijauan sekolah. Faktor pendukung pelaksanaan strategi meliputi dukungan kepala sekolah, ketersediaan sarana dan prasarana, program sekolah yang mendukung, serta kerja sama antar siswa. Sementara itu, faktor penghambat meliputi rendahnya kesadaran sebagian siswa, keterbatasan waktu pembelajaran, pengaruh lingkungan luar sekolah, dan keterbatasan fasilitas tertentu. Temuan penelitian menunjukkan bahwa pembentukan karakter peduli lingkungan pada siswa sekolah dasar memerlukan penerapan strategi yang beragam, konsisten, dan terintegrasi dengan budaya sekolah agar nilai-nilai kepedulian lingkungan dapat diinternalisasikan dalam aktivitas sehari-hari siswa.